2013
DOI: 10.1177/1535370213511022
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol-induced autophagy in malignant mammary cancer cells

Abstract: γ-Tocotrienol, a member of the vitamin E family of compounds, displays potent antiproliferative and cytotoxic effects in a variety of cancer cell types at treatment doses that have little or no effect on normal cell viability or growth. Autophagy is a tightly regulated lysosomal self-digested process that can either promote cell survival or programmed cell death, but the role of autophagy in mediating γ-tocotrienol-induced cytotoxicity in breast cancer is not presently completely understood. Mouse (+SA) and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 50 publications
3
61
2
Order By: Relevance
“…34,35) This stock γ-tocotrienol solution was then used to prepare different concentrations of treatment media.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…34,35) This stock γ-tocotrienol solution was then used to prepare different concentrations of treatment media.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…Membranes were then blocked and incubated with specific primary antibodies diluted 1 : 1000 to 1 : 5000 as described previously. 35) Membranes were then washed and incubated with their respective horseradish-peroxide conjugated secondary antibodies diluted 1 : 5000. Immunocytochemical Fluorescence Staining MDA-MB-231 and +SA cells were initially plated at 2×10 4 cells/ chamber in 8-chamber glass (BD Falcon, San Jose, CA, U.S.A.) and maintained in control media.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…10) γ-Tocotrienol is a member of the vitamin E family of compounds that displays potent anticancer effects at treatment doses that have little or no effect on normal cell viability. [11][12][13][14][15][16] Previous studies have shown that γ-tocotrienol significantly decreases growth factor receptor mediated activation of the PI3K/Akt/mTOR pathway. 14,17,18) Recently, it has also been shown that exposure to tocotrienols decreases c-Myc protein levels, [18][19][20] and block compensatory increases in HIF-1α during hypoxic conditions in cancer cells.…”
mentioning
confidence: 99%